Nucleotide sequence of the upstream regulatory region of BoLA-DRB - Ripoli, María Verónica (2002)
The sequence of the proximal upstream regulatory region (URR) of the bovine DRB genes was amplified using oligonucleotide primers designed from the consensus among DRB sequences from different species. The obtained DNA sequence was 234 bp long and composed of highly conserved sequence motifs, showing the same organization as the HLA-DRB, H2-IAb, H2-IEb and ELA-DRB genes. In this paper we report the sequence of the proximal upstream regulatory region (URR) of the bovine DRB genes. These are the first sequence data on the upstream regulatory regions of MHC class II genes in cattle. The reverse oligonucleotide primer (5′-GAGAAATA-CAGACACACCATGC-3′) was designed from the consensus among DRB sequences from different species: BoLA-DRB (accession numbers U77067-68, U78548 and D45357), SLA-DRB (M55165-6), HLA-DRB (S72812 and L07838-40), H2-IEb and H2-IAb (X86151-6). As a forward primer we used the oligonucleotide proposed by Turco et al. (1990) (5′-TGTTTCAGAAAAGGACCTTC-3′), which was designed from the consensus among HLA-DRB sequences corresponding to the promoter region of the DRB genes. A polymerase chain reaction (PCR) was carried out in a total volume of 25 μl comprising 2.5 mM MgCl2 Tris-HCl (pH = 8.4), 50 mM KCl, 100 μM of each dNTP, 0.5 μM of each primer, 1.0 unit Taq polymerase (Gibco BRL, Life-Technologies, Grand Island, NY) and 50-100 ng DNA template. The genomic DNA was extracted from whole blood from one animal of the Saavedreño Creole breed. The amplification profile consisted of 1 min at 94°C, followed by 30 cycles of 45 s at 94°C, 45 s at 55°C and 45 s at 72°C, with a final extension of 3 min at 72°C. The amplification products were cloned into a dT-tailed pGEM-T easy vector (Promega, Madison, WI), and three clones of each PCR product were sequenced on an Applied Biosystems 377 automated sequencer (Bio-Resource Center, Cornell University, Ithaca, NY), using a T7 universal primer. All the sequenced clones exhibited 100% sequence similarity to each other. The nucleotide sequence of the proximal upstream control region of the BoLA-DRB genes (GenBank accession number AY040327) was 234 bp long and composed of highly conserved sequence motifs that included, from the 5′ to the 3′ direction, W, X, Y, CCAAT and TATA-like boxes (Fig. 1), showing the same organization of the conserved regulatory elements as the HLA-DRB, H2-IAb, H2-IEb and ELA-DRB genes (e.g. Louis et al., 1993, 1994; Singal et al., 1993; Singal & Qiu, 1994). Furthermore, the BoLA-DRB URR nucleotide sequence had higher identity with HLA-DRB sequences than with HLA-DQB sequences (data not shown). This suggests that the sequence AY040327 corresponds to a BoLA-DRB promoter. However, we are still unable to assign this sequence to a specific BoLA-DRB gene, as at least three BoLA-DRB genes have been reported to exist (Andersson et al., 1986; Muggli-Cocket & Stone, 1988). BoLA-DRB3 is the most expressed DRB gene in cattle, while DRB1 is expressed at a low level and DRB2 is a pseudogene (Burke et al., 1991).